DIGITAL LEADERSHIP IN THE ERA OF DIGITAL TRANSFORMATION: A SYSTEMATIC LITERATURE REVIEW OF SCOPUS-INDEXED PUBLICATIONS FROM 2020-2024 - Haka, Eddy Aprianto; Kristiyano, Agung; Firdaus, Jhon; Suswanti, Tutik; Sukmayadi, Yudi; Sembodo, Joko; Wahyudianto, Eko (Ikatan Dosen Menulis, 2024)
This study presents a systematic review of digital leadership research from 2020 to 2024, analyzing literature indexed in Scopus to understand the evolution, components, and implications of digital leadership in contemporary organizations. Through comprehensive analysis of publication trends and thematic development, the research identifies four key competency domains: technical, strategic, human-centric, and adaptive capabilities. The findings reveal a significant evolution from basic technical skills to an integrated leadership approach that combines technological proficiency with strategic vision and human-centered management. The study demonstrates that successful digital leaders integrate multiple competencies and adapt their leadership style to specific organizational contexts. Analysis of 235 publications shows a substantial increase in digital leadership research, with emerging focus areas including artificial intelligence integration, virtual team management, and digital transformation strategies. The research provides practical implications for organizations developing digital leadership capabilities and offers a framework for future research directions. The findings indicate that organizations with well-developed digital leadership are significantly more successful in achieving digital transformation objectives and maintaining competitive advantage in the digital age.